1946
DOI: 10.1128/jb.51.1.95-105.1946
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Action of Penicillin and the Sulfonamides in Vitro : The Nature of the Reaction

Abstract: The combined action of penicillin and the sulfonamides against bacteria has been demonstrated by several workers. Ungar (1943) reported that penicillin and sulfapyridine showed a marked additive effect both in vitro and in vivo against Staphylococcus aureus and hemolytic streptococci. Soo-Hoo and Schnitzer (1944) reported the additive effect of penicillin when combined with sulfanilamide or sulfapyridine against streptococci. Kirby (1944) using sulfadiazine and Bigger (1944) using sulfathiazole found that thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1946
1946
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The relationship between synergism and drug resistance has been previously indicated by us in a report on the combined action of penicillin and the sulfonamides (Klein and Kalter, 1945). It was found that an important factor in the observed synergism was the ability of a small amount of an added drug, in this case the sulfonamide, to prevent the' multiplication of the few bacteria resistant to the test concentration of penicillin.…”
Section: Discussionmentioning
confidence: 73%
“…The relationship between synergism and drug resistance has been previously indicated by us in a report on the combined action of penicillin and the sulfonamides (Klein and Kalter, 1945). It was found that an important factor in the observed synergism was the ability of a small amount of an added drug, in this case the sulfonamide, to prevent the' multiplication of the few bacteria resistant to the test concentration of penicillin.…”
Section: Discussionmentioning
confidence: 73%
“…We have previously shown that in the case of penicillin and the sulfonamides (Klein and Kalter, 1946) an important factor in the observed synergism resulted from the ability of a relatively low concentration of one chemotherapeutic agent to inhibit the small number of bacteria resistant to the other chemotherapeutic agent. In experiments which we will report at a later date we have found that bacteria resistant to streptomycin are still susceptible to penicillin and the sulfonamides, and that in vitro a combination of streptomycin with penicillin or sulfonamides, or both, was more effective than either agent alone.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate justification for combined therapy then should be based on a combined effect that is greater than that achieved by the safe maxmum dosage of either drug alone. One rationale that appeared to justify combined therapy in infections due to a single agent was the inhibition of the development of drug resistance (Klein and Kalter, 1946; Klein and Kimmelman, 1947). The concept may be stated as follows: All bacterial populations show variation in the susceptibility of their individual cells to a given concentration of an antibiotic (Demerec, 1945; Klein, 1947).…”
mentioning
confidence: 99%
“…Combinations of sulfonamides, penicillin, streptomycin, and p-aminosalicylic acid have been used quite extensively, and apparently the results have been considered satisfactory though controlled clinical studies on combined therapy are quite limited. One reservation concerning the use of combined drugs was pointed out in an earlier publication (Klein and Kalter, 1946; see also Chain and Duthie, 1945). It was shown that under certain conditions antagonism, as demonstrated by a significant inhibition of the bactericidal and lytic action of penicillin by an added sulfonamide, could be shown to occur in vitro.…”
mentioning
confidence: 99%